Safety of methanethiol [12.003] when used as a feed additive for all animal species - EFSA Panel on Additives and Products or Substances used in Animal Feed (FEEDAP); Vasileios Bampidis; Giovanna Azimonti; Maria de Lourdes Bastos; Henrik Christensen; Birgit Dusemund; Mojca Fašmon Durjava; Maryline Kouba; Marta López‐Alonso; Secundino López Puente; Francesca Marcon; Baltasar Mayo; et al. (EFSA Journal, 2020)
Abstract Following a request from the European Commission, the EFSA Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) was asked to deliver a scientific opinion on the safety of methanethiol [12.003] belonging to chemical group 20 (aliphatic and aromatic mono‐ and di‐thiols and mono‐, di‐, tri‐ and polysulfides with or without additional oxygenated functional groups). Methanethiol [12.003] is currently authorised as a flavour in food. The additive under assessment is safe for all animal species up to the maximum proposed use level of 0.05 mg/kg complete feed. No concerns for the consumer and the environment were identified following the use of the additive at the proposed conditions of use in feed. Methanethiol [12.003] should be considered as irritant to skin and eyes and to the respiratory tract. No conclusions can be drawn on skin sensitisation.